End User’s Computing Satisfaction Untuk Sistem Informasi Obat Bahan Alam Pada Tenaga Vokasi Farmasi Sebagai Pengguna Di Kota Semarang - Ratu, Modestus; Suwarni, Sri; Wulandari, A. Ratna; Aditya, Martanty; Santoso, Arif (Jurnal Farmasi & Sains Indonesia, 2025)
The use of herbal medicine is a method of treatment that utilizes plants, either empirically by the community or with the help of information from healthcare professionals. This research aims to evaluate the level of satisfaction and the strength of the relationship between the dimensions of satisfaction using the End User’s Computing Satisfaction method by Pharmacy Vocational Personnel towards the Natural Herbal Medicine Information System (SI-OBAL) in Semarang City. This research is a non-experimental study with the EUCS method, which is qualitatively quantified prospectively. The instrument used was a questionnaire that has been tested by experts and through validation and reliability testing. The data was analyzed using frequency statistics to describe the characteristics of the respondents and the percentage of each dimension, which includes end-user satisfaction with technological aspects such as content, accuracy, format, timeliness, and ease of use of the system. The results of the study show that the overall level of satisfaction of Pharmacy Vocational Personnel with the Natural Herbal Medicine Information System (SI-OBAL) is 84.19%, which is categorized as very satisfied. This indicates that SI-OBAL has successfully met the needs and satisfaction of Pharmacy Vocational Personnel in Semarang City.